Delineating the phenotypic spectrum of hyperphosphatasia with mental retardation syndrome 4 in 14 patients of Middle‐Eastern origin. Issue 12 (22nd October 2018) - Balobaid, Ameera; Ben‐Omran, Tawfeg; Ramzan, Khushnooda; Altassan, Ruqaiah; Almureikhi, Mariam; Musa, Sara; Al‐Hashmi, Nadia; Al‐Owain, Mohammed; Al‐Zaidan, Hamad; Al‐Hassnan, Zuhair; Imtiaz, Faiqa; Al‐Sayed, Moeenaldeen
Abstract: Hyperphosphatasia with mental retardation syndrome 4 (HPMRS4) is a rare autosomal recessive condition caused by an impairment of glycosylphophatidylinositol biosynthesis. The cardinal features of HPMRS4 include; characteristic facial features, severe intellectual disability and various neurologic abnormalities. We report here detailed clinical, biochemical, and molecular findings of 14 patients clinically suspected to have HPMRS4, from three Middle‐Eastern Countries; Saudi Arabia, Qatar, and Oman. All patients in our series presented with the cardinal features pointing to HPMRS4 and with an elevated alkaline phosphatase level. Five patients had megalocornea, which have been reported recently in an Arab patient. Additionally, fracture, bilateral coxa valga, camptodactyly, truncal obesity, and hyperpigmented macules of the upper thigh, each was seen once and was not described before with HPMRS4. Additional clinical and radiological findings are described, supporting the novel clinical and radiological findings recently described in Egyptian patients. The utilization of homozygosity mapping coupled with PGAP3 sequencing and whole exome sequencing facilitated the mutation detection in these patients. These missense mutations include c.320C > T (p.S107 L), c.850C > T (p.H284Y), and c.851A > G (p.H284R) in the PGAP3 gene. We believe that the recurrent mutations identified in our cohort may represent founder mutations in big tribes from a certain geographical region of Saudi Arabia, Qatar, and Oman. Therefore, in case of a clinical suspicion of HPMRS4 in these populations, targeted genetic testing for the identified mutations should be performed first to expedite the genetic diagnosis.